Banana Wine - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Bananas, long used for making beer in Rwanda, are being converted to wine with the appellation controlee <<MiUe Collines (thousand hills). Rwanda produces a million tons of bananas each year, of which eight tons a day are converted to beer. The...